Evaluation of economic efficiencies in clinical retina practice: activity-based cost analysis and modeling to determine impacts of changes in patient management - Murray TG (Dove Medical Press, 2011)
Timothy G Murray1, Paul Tornambe2, Pravin Dugel3, Kuo Bianchini Tong41Bascom Palmer Eye Institute, Miami, FL, USA; 2Tornambe Eye Institute, San Diego, CA, USA; 3Retinal Consultants of Arizona, Peoria, AZ, USA; 4Quorum Consulting, San Francisco, CA, USABackground: The purpose of this study is to report the use of activity-based cost analysis to identify areas of practice efficiencies and inefficiencies within a large academic retinal center and a small single-specialty group. This analysis establishes a framework for evaluating rapidly shifting clinical practices (anti-vascular endothelial growth factor therapy, microincisional vitrectomy surgery) and incorporating changing reimbursements for care delivery (intravitreal injections, optical coherence tomography [OCT]) to determine the impact on practice profitability. Pro forma modeling targeted the impact of declining reimbursement for OCT imaging and intravitreal injection using a strategy that incorporates activity-based cost analysis into a direct evaluation schema for clinical operations management.Methods: Activity-based costing analyses were performed at two different types of retinal practices in the US, ie, a small single-specialty group practice and an academic hospital-based practice (Bascom Palmer Eye Institute). Retrospective claims data were utilized to identify all procedures performed and billed, submitted charges, allowed charges, and net collections from each of these two practices for the calendar years 2005–2006 and 2007–2008. A pro forma analysis utilizing current reimbursement profiles was performed to determine the impact of altered reimbursement on practice profitability. All analyses were performed by a third party consulting firm.Results: The small single-specialty group practice outperformed the academic hospital-based practice on almost all markers of efficiency. In the academic hospital-based practice, only four service lines were profitable, ie, nonlaser surgery, laser surgery, non-OCT diagnostics, and injections. Profit margin varied from 62% for nonlaser surgery to 1% for intravitreal injections. Largest negative profit contributions were associated with office visits and OCT imaging.Conclusion: Activity-based cost analysis is a powerful tool to evaluate retinal practice efficiencies. These two distinct practices were able to provide significant increases in clinical care (office visits, ophthalmic imaging, and patient procedures) through maintaining efficiencies of care. Pro forma analysis of 2011 data noted that OCT payments to facilities and physicians continue to decrease dramatically and that this payment decrease further reduced the profitability for the two largest aspects of these retinal practices, ie, intravitreal injections and OCT retinal imaging. Ultimately, all retinal practices are at risk for significant shifts in financial health related to rapidly evolving changes in patterns of care and reimbursement associated with providing outstanding clinical care.Keywords: retinal practice, practice utilization, activity-based cost analysis, pro forma modeling